Case report: Fully endoscopic microvascular decompression for glossopharyngeal neuralgia - Jiang, Haotian; Zhou, Dewei; Wang, Pan; Zeng, Longwei; Liu, Jie; Tang, Chao; Zhang, Gang; Tan, Xiaorong; Wu, Nan (Frontiers in Surgery, 2023)
With the advances in endoscopic technology, endoscopy is widely used in many neurosurgical procedures, such as microvascular decompression, which is an effective method to treat glossopharyngeal neuralgia, trigeminal neuralgia, and facial spasm. The purpose of this study was to determine the efficacy of fully endoscopic microvascular decompression in the treatment of glossopharyngeal neuralgia. We managed a patient with glossopharyngeal neuralgia in our department, whose main clinical manifestation was recurrent left ear and facial pain for 3 years. The patient underwent a fully endoscopic microvascular decompression. The pain in the left ear and face was significantly relieved postoperatively, and there was no recurrence at the 6-month follow-up evaluation. We describe a case of glossopharyngeal neuralgia that was successfully treated by fully endoscopic microvascular decompression, which showed that endoscopy has advantages in microvascular decompression, and fully endoscopic microvascular decompression is an effective method for glossopharyngeal neuralgia.